Mobile Library Application in Indonesia’s Digital Libraries - Dinazzah, Asma Rakha'; Rahmi, Rahmi (Journal of Education Technology, 2022)
Increasing mobile device usage in the 21st century, coupled with the COVID-19 pandemic, continue to change various sectors, including libraries. A library is a place to find information, both in-person and online. Ideally, a library should develop and improve each year to ensure optimal service provision to its users. The development of mobile phone applications is a trend that has revolutionized how consumers access information in a variety of sectors, including libraries. This study aims to analyse the development of mobile library applications (m-library apps) in digital libraries in Indonesia, using a descriptive and qualitative methodology. Each m-library application’s existence was verified using the attached link or the search feature on the Google Play Store. The results are described descriptively with a focus on the analysis of applications used by m-libraries. The results indicate that Indonesia’s digital libraries are currently showing progress, marked by libraries in Indonesia that have started using m-library applications in their digital libraries. The most widely used applications by digital libraries in Indonesia typically used third party vendors to develop their applications, such as Kubuku Resources, PT, Enam Kubuku Indonesia, Gramedia Asri Media and Bina Pustaka. Our results also highlight a need for continuous improvement in m-library applications, in terms of adding both internal (e.g., preservation and security) and external (e.g., user training and promotional factors) features.